THE INFLUENCE OF PERSONALITY TRAITS, TIMING, AND INTERACTIVITY ON PURCHASING DECISIONS FOR SKIN SAKE PRODUCTS - Michelle Putri Supriyanto (STMIK Indonesia Banda Aceh, 2026)
The development of digital marketing has driven the use of live streaming commerce as an increasingly popular marketing strategy, particularly in the skincare industry, which emphasizes visuals and direct interaction with consumers. However , the effectiveness of live streaming in driving purchasing decisions still shows mixed results for local skincare brands . This study was designed to evaluate the impact of personality traits, live broadcast time , and the level of interactivity on consumer choices in purchasing For Skin Sake (FSS) products . A quantitative approach was applied through a survey targeting TikTok users in Greater Jakarta (Jabodetabek) who had watched FSS live streaming sessions . The results revealed that all three variables had a positive influence on purchasing decisions , with interactivity being the most prominent factor . These findings emphasize that the effectiveness of live streaming is not solely determined by technological aspects , but also by the quality of interaction , the nature of the host , and the right broadcast time . The contribution of this study is expected to enrich the theory in the field of digital marketing and provide practical guidance for local skincare brands in developing their product content. a more efficient live streaming strategy .